1976
DOI: 10.2466/pms.1976.43.2.459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Imipramine and Methylphenidate on Perceptual-Motor Performance of Hyperactive Children

Abstract: Perceptual-motor effects of imipramine and methylphenidate were evaluated in a double-blind study of 47 hyperactive children. No effects were found for imipramine, although methylphenidate improved performance on several tests. Improvement due to methylphenidate was not related to baseline scores. A discriminant function was computed to compare baseline perceptual-motor scores of the hyperactive and 41 normal children. Only half of the hyperactive children were clearly discriminated from normal children by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Although performance of ADI/D chl1dren did not differ slgniflcantly from normal controls on a 12 word llst (Benezra & Douglas, 1988), Douglas and Peters (1979) reported slgnificant impairment of recall of a 34 ward list and O'Neill and Douglas (ln preparation) found significant normal-ADIID differences on a 24 word llst. Slmllar1y, Spring, Yellin, and Greenberg (1976) reported impaired recall of Digit Span by ADIID children when an extended form of the tasK was used. Ceci and Tishman (1984) found that ADHD chlldren recalled central and task irrelevant Information as weIl as or better than normal controls on simple tasks.…”
mentioning
confidence: 99%
“…Although performance of ADI/D chl1dren did not differ slgniflcantly from normal controls on a 12 word llst (Benezra & Douglas, 1988), Douglas and Peters (1979) reported slgnificant impairment of recall of a 34 ward list and O'Neill and Douglas (ln preparation) found significant normal-ADIID differences on a 24 word llst. Slmllar1y, Spring, Yellin, and Greenberg (1976) reported impaired recall of Digit Span by ADIID children when an extended form of the tasK was used. Ceci and Tishman (1984) found that ADHD chlldren recalled central and task irrelevant Information as weIl as or better than normal controls on simple tasks.…”
mentioning
confidence: 99%
“…Hyperactive subject's scores were depressed on the Attentional-Concentration score, but not on the other scores (cf. Spring et al, 1976).…”
Section: Higher-order Cognitive Test Performancementioning
confidence: 95%
“…A reviewer (Horn, 1972) describes this score as the "capacity or inclination to sustain attention in the face of the difficulty involved in resolving moderately complex spatial relations" (p. 756). The T-score has been shown to differentiate hyperactive from normal subjects (Spring et al, 1976) and in clinical trials with cerebral stimulants, the T-score is drug sensitive (Conners, Eisenberg, & Sharpe, 1963;Conners & Rothschild, 1968;Conners et al, 1969;Epstein, Lasagna, Conners, & Rodriguez, 1968).…”
Section: Simple Performance Testsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, one study demonstrated that imipramine did not produce changes in perceptual-motor performance tasks beyond those seen with a placebo, whereas Ritalin significantly improved performance (e.g., Spring, Yellin, & Greenberg, 1976).…”
Section: Tricyclic Antidepressants (Desimpramine Imipramine)mentioning
confidence: 99%